NORMS OF INTERNATIONAL LAW IN THE SPHERE OF INTELLECTUAL PROPERTY TO IMPROVE NATIONAL LEGISLATION THROUGH THEIR IMPLEMENTATION (Academicia Globe: Inderscience Research, 2022)
The article analyzes the issues of legal regulation of intellectual property objects. In addition, it is considered topical issues of the implementation of international law in the field of intellectual property in national legislation.